Adaptation and research development in the spectrum of methods with advanced access in the area of communication and computer system - Zeqiri, Nderim (Journal of Advanced Computer Science & Technology, 2013)
In some models that set new principles of work, there appears to require the implementation and adaptation of computer resources in terms of hardware and software adaptation. This method entails the extension of the current system versus research perspectives in the context of programs, models and restructuring in line with other development, hardware or software, or adjustment to learning in electronic form; the interaction of many processes, to create a sustainable system through increased research and adoption of safety and suitability. So in this paper we present models and alternative approaches to achieve a better perspective in the field of restructuring and adjustment of the model with the program and hardware resources. In many cases is needed a quick access method which is specified in the context of generating appropriate values ??for digital systems